Comprehensive Evaluation of Genital Prolapse — A Clinical Perspective (The Planet, 2024)
Introduction: Genital prolapse is a prevalent and multifaceted medical condition that significantly impacts the quality of life for affected individuals, predominantly women. This study provides an overview of a comprehensive clinical perspective on the evaluation of genital prolapse. The evaluation process begins with a detailed medical history, encompassing factors such as parity, previous pelvic surgeries, and relevant medical conditions. Methods and materials: This cross-sectional study was conducted in the obstetrics and gynecology department at the Shaheed Tajuddin Ahmad Medical College Hospital in Gazipur, Bangladesh. The research was carried out between January and December of 2019. All information was gathered by standardized questionnaires, including all relevant factors, physical examinations, and interviews. The statistical package for social science (SPSS) program was used for statistical analysis following data collection. Result: The study revealed that 100% of patients had a history of vaginal delivery. Notably, 90% of these deliveries occurred at home and 44% of patients experiencing prolonged labor. Uterine prolapse severity analysis indicated that 80% of patients exhibited a 2nd degree of prolapse. Conclusion: Childbirth-related injuries, particularly among homemakers with limited education, were identified as the predominant cause of acquired vaginal prolapse in a recent study. Common patient conditions included stress incontinence, moderate rectocele, and cystocele. Post-surgery, complications like fever and urinary tract infections were more common, but a significant 94.0% of cases reported complete relief after intervention.
Keywords: Genital Prolapse; Prolonged Labor; Parity; Hysterectomy